1987
DOI: 10.1126/science.237.4813.389
|View full text |Cite
|
Sign up to set email alerts
|

The 30-Kilodalton Gene Product of Tobacco Mosaic Virus Potentiates Virus Movement

Abstract: The proposed role of the 30-kilodalton(kD) protein of tobacco mosaic virus is to facilitate cell-to-cell spread of the virus-during infection. To directly define the function of the protein, a chimeric gene containing a cloned complementary DNA of the 30-kD protein gene was introduced into tobacco cells via a Ti plasmid-mediated transformation system of Agrobacterium tumefaciens. Transgenic plants regenerated from transformed tobacco cells expressed the 30-kD protein messenger RNA and accumulated 30-kD protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
234
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(242 citation statements)
references
References 43 publications
6
234
0
2
Order By: Relevance
“…With respect to the 58K and 48K proteins, this result was not unexpected. These proteins show a limited homology with the 30K transport protein of tobamoviruses (Meyer et al, 1986;Deom et al, 1987;Meshi et al, 1987). Furthermore the 48K protein is found in the membrane fraction of infected leaves (Wellink et al, 1987) and recent results with immunogold labelling of sections of infected leaves with anti-48K serum have revealed an association of this protein with tubular structures protruding from the cell wall (J. van Lent, unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…With respect to the 58K and 48K proteins, this result was not unexpected. These proteins show a limited homology with the 30K transport protein of tobamoviruses (Meyer et al, 1986;Deom et al, 1987;Meshi et al, 1987). Furthermore the 48K protein is found in the membrane fraction of infected leaves (Wellink et al, 1987) and recent results with immunogold labelling of sections of infected leaves with anti-48K serum have revealed an association of this protein with tubular structures protruding from the cell wall (J. van Lent, unpublished results).…”
Section: Discussionmentioning
confidence: 94%
“…Transgenic plants that accumulate the MP of TMV can complement mutants of TMV that do not produce functional MP (Deom et al, 1987;Holt and Beachy, 1991). The coat protein (CP) is not required for cell-to-cell movement (Dawson et al, 1988), although it is required for systemic spread in most hosts (Dawson, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A part of the putative 34.3K protein of PPV-NAT was found to be slightly homologous to the 30K protein of tobacco mosaic virus (TMV; Meshi et aL, 1982). Deom et al (1987) demonstrated that expression of the 30K protein of TMV in transgenic tobacco plants could play a role in cell-to-cell spread during virus infection. This suggests that the 34-3K protein could have a similar function.…”
Section: Coding Regionsmentioning
confidence: 99%